Genetic Variability Studies on Drought Tolerance using Agro- Morphological and Yield Contributing Traits in Rapeseed-Mustard - Sharma, A.; Kumari, V.; Rana, A. (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted during rabi season (October-May), 2018−2019 at the Experimental Farm of Department of Genetics and Plant Breeding, CSK HPKV, Palampur (HP), India to develop reliable selection criteria for drought tolerance. 25 advanced breeding lines of different Brassica species were used to determine their mean performance, components of variability, heritability and genetic advance under moisture stress conditions created at rosette stage, flower initiation stage and siliqua formation stage using various agro-morphological and yield contributing traits. Sufficient genetic variability was found for almost all the characters except for 1000-seed weight under non-stress stage conditions. Estimates of parameters of variability revealed that phenotypic coefficients of variation were higher than their respective genotypic coefficients of variation. Under moisture stress conditions, high heritability coupled with high genetic advance was observed for number of secondary branches plant-1 in non-stress and all the moisture-stress stages. Siliqua formation stage was found most susceptible to moisture stress conditions which also led to maximum reduction in seed yield. Using drought susceptibility index, the genotypes HPBS-1 followed by HPKM-04-1 were found to be moderately drought tolerant as these exhibited the lowest drought susceptibility index value in Stage-I and Stage-III while in Stage-II, RCC-4×Varuna followed by HPBS-1 exhibited lowest drought susceptibility index value. Therefore, systematic characterization of differences in physiological responses to drought stress among elite lines is helpful in understanding mechanisms of drought resistance. Hence, traits like primary branches plant-1, secondary branches plant-1, siliquae plant-1, seeds siliqua-1, seed yield plant-1 and 1000-seed weight can be further used in selection criteria for future breeding programme aimed for enhancing drought tolerance.